A food sovereignty critique of the G8 New Alliance on food security and nutrition - Crankshaw, Amy (My University, 2016)
The G8 New Alliance on Food Security and Nutrition (NAFN) is a new, under-researched and rapidly spreading partnership initiative. As the latest attempt to target hunger in Africa by developed countries, it deserves a certain level of scrutiny to decipher the intended development trajectory for African food systems and the possible implications for smallholder farmers, since these smallholders produce more than ninety percent of the continent’s food supply. Food sovereignty provides the ideal lens through which to analyse the New Alliance, being a political economy critique of agro-industrial food systems, as well as a constitutive approach to rights and the building of a grassroots movement and alternative. This research seeks to ascertain how the New Alliance may globalise African agriculture and undermine food sovereignty. An exploratory research design was used, first historicising African globalised agriculture, then decoding the main objectives of the New Alliance, and finally using the African Food Sovereignty Alliance as a case study to critique its translation into African countries’ commitments. The first few predictions of the hypothesis were strongly validated with findings that the New Alliance will result in large-scale investment of land, the commercialisation of the seed industry and an increased use of agro-chemicals and GMOs, increased foreign investment, and monopolisation of agribusiness by MNCs. To a lesser degree, the prediction that it would decrease barriers to trade and increase imports and exports was confirmed; however, there was little evidence that it intends to cut domestic support measures like some previous development programmes. The New Alliance is beyond reform, built on flawed neoliberal assumptions about development. This and further research could contribute to a movement to abolish the New Alliance before it induces negative long term effects, and to warn off other African countries contemplating this initiative.
International Relations Masters Research Thesis, 2015 University of Witwatersrand
Keywords: Group of Eight (Organization); Food security--Africa; Food sovereignty--Africa; Sustainable agriculture